The Phenomenon of Jilboobs in Generation Z in the Era of Society 5.0 - Amiruddin, Wildan (Yayasan Pesantren Mahasiswa An-Nur, 2024)
Generation Z was born amidst the development of technology. So this generation is more sophisticated. Their thinking is more tolerant of new paradigms. Technological advances like now are easily followed by them because of their close relationship, especially with the internet. The internet was previously used as a medium of information, but for Gen Z the internet was then used as a medium to socialize with each other. This is where Social Media came from. In its development, social media became the second brother for Gen Z. For them, social media has become a daily necessity. If they don't open social media, they will be left behind. They have a position as the main users of social media. This is manifested in the rise of new professions such as YouTubers and TikTokers. Whereas this profession was not found in the previous generation, namely the millennial generation. This is an integral part of society 5.0 which uses the concept of internet development as an orientation to a better human life. On the other hand, the impact of using social media that always wants a lot of comments, likes, and viewers makes Gen Z forget religious norms such as covering the aurat for women perfectly. So the jilboobs phenomenon arose, which prioritizes body orientation by accentuating certain parts. The main goal is to increase comments, likes and viewers. Seeing this phenomenon, researchers try to interpret it so that the reason Gen Z does this is answered by interpreting denotation, connotation, and metaphor.